2016
DOI: 10.1177/2047487316643446
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the post-training oxygen uptake efficiency slope in patients with coronary artery disease

Abstract: Background: Peak oxygen uptake is an independent predictor of mortality in patients with coronary artery disease (CAD). However, patients with CAD are not always capable of reaching peak effort, and therefore submaximal gas exchange variables such as the oxygen uptake efficiency slope (OUES) have been introduced. Baseline exercise capacity as expressed by OUES provides prognostic information and this parameter responds to training. Therefore, we aimed to assess the prognostic value of post-training OUES in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Key CPET parameters like trueV˙O2peak, OUES, and O 2 pulse (including O 2 pulse trajectory) are highly relevant predictors of mortality and morbidity in CHD patients . Structured exercise training regardless of training modality has proven to improve these parameters . However, in our study only patients in the HIIT group showed a substantial trueV˙O2peak improvement and reached a normal age‐predicted trueV˙O2peak after completion of the program with the identical level of exhaustion (ie, RER) as compared to the usual care group.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Key CPET parameters like trueV˙O2peak, OUES, and O 2 pulse (including O 2 pulse trajectory) are highly relevant predictors of mortality and morbidity in CHD patients . Structured exercise training regardless of training modality has proven to improve these parameters . However, in our study only patients in the HIIT group showed a substantial trueV˙O2peak improvement and reached a normal age‐predicted trueV˙O2peak after completion of the program with the identical level of exhaustion (ie, RER) as compared to the usual care group.…”
Section: Discussionsupporting
confidence: 90%
“…Key CPET parameters like trueV˙O2peak, OUES, and O 2 pulse (including O 2 pulse trajectory) are highly relevant predictors of mortality and morbidity in CHD patients . Structured exercise training regardless of training modality has proven to improve these parameters .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although encouraging, the data supporting the prognostic value of OUES is limited to date due to a lack of appropriately powered prospective studies and warrants further investigation. The OUES displays prognostic value in patients with HF [49][50][51] and coronary artery disease (CAD) [52,53] and has been shown to be responsive to physical training in patients with CAD [54,55].…”
Section: Oxygen Uptake Efficiency Slopementioning
confidence: 99%
“…1) The oxygen uptake efficiency slope (OUES) reflects the rate of increase of the logarithmically transformed ventilation in response to a given increase in oxygen uptake and it correlates highly with VO 2 peak in cross sectional studies [9]. The OUES is a prognostic marker in patients with chronic heart failure and coronary artery disease [10, 11], which both are common comorbidities of COPD [12]. 2) The ventilatory efficiency slope (ΔVE/ΔVCO 2 ), which represents the increase in ventilation for a given rise in carbon dioxide production, is increased when ventilation perfusion mismatching occurs, in case of diffusion abnormalities or with an excess dead space ventilation.…”
Section: Introductionmentioning
confidence: 99%